Problematika Manajemen Pengelolaan Sampah Kota Pekanbaru Tahun 2016 - Isril; Rury Febrina (Laboratorium Jurusan Ilmu Pemerintahan FISIP Universitas Riau, 2017)
The development dynamics of Pekanbaru City is so rapid and accompanied by rapid population growth has brought consequences on increasing the volume of waste from the community. The rapid growth of population, industry, investment and trade in Pekanbaru City produces domestic waste of approximately 1,100 tons per day. With the amount of waste generated in such a way, the environmental conditions of Pekanbaru City, especially the community settlements, fall into the category of complex hygiene issues. The Waste Management consisting of Planning, Organizing, Staffing, Motivating, and Supervision/Controlling.